Chemoradiation therapy for localized colorectal cancer: a view from the outside - F. Sh. Akhmetzyanov; V. I. Egorov; G. R. Abdulganieva (Сибирский онкологический журнал)
Background. Colorectal cancer is among the most lethal and prevalent malignances in the world. The management of localized colorectal cancer is highly debated. Surgical resection of the rectum, such as total mesenteric excision (TME) is usually associated with significant morbidity and mortality. The integration of various chemotherapy options into the standard treatment of localized rectal cancer could potentially enhance the tumor control with a subsequent reduction in the frequency of recurrence, thus improving overall and disease-free survival. Moreover, there are categories of patients for whom surgical treatment is contraindicated and chemotherapy will be more useful for them. Although rectal cancer is predominantly a disease of older patients, current guidelines do not incorporate optimal treatment recommendations for elderly patients with comorbidities; therefore this issue remains a matter of debate.Aim. We aimed to consider alternative approaches to the treatment of localized rectal cancer and the management of selected patients with this diagnosis.Material and Methods. We searched for publications in the Pubmed, eLibrary databases and up-to-date information on the basis of world cancer associations.Conclusions. Comparison of surgery with concurrent chemoradiotherapy for localized rectal cancer showed that in some cases neoadjuvant therapy can be useful and successful, acting as an ideal alternative. However, this approach may be suitable for selected patients who meet certain criteria. In addition, a follow-up care after treatment should include a specific range of diagnostic imaging tests.